(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
This article investigates the functional capabilities of zoonymic language units in text formation in English and Uzbek. Zoonymic units, which include lexical and phraseological expressions containing animal names, play an important role in representing nationalcultural worldviews, emotional evaluation, and stylistic expressiveness. The study aims to identify the semantic, stylistic, and linguocultural functions of zoonymic components in literary and everyday discourse. Comparative, contextual, semantic, and linguocultural analysis methods are employed in the research. The findings demonstrate that zoonymic units in both languages serve as effective means of characterization, emotional evaluation, metaphorical representation, and text cohesion. Despite certain universal semantic associations, English and Uzbek zoonymic expressions reveal significant national-cultural differences shaped by historical traditions, social values, and collective mentality. The article concludes that zoonymic language units constitute an important linguocultural layer and actively participate in text formation processes in both languages.